Digital Literacy, Customer Loyalty and Retention in B2C Healthcare Services: Evidence from Indian Digital Healthcare Consumers - Neerajana Sai Niveditha Gergi; P. Mohan Reddy (Journal of Economics, Management and Trade, 2026)
While digitalisation in India is expanding opportunities for consumers to access diagnostic, consultation and pharmacy services through Business-to-Consumer (B2C) platforms, it is uncertain whether they will use the same service in the future. The study aimed to determine whether digital literacy is correlated with customer loyalty among Indian consumers of B2C healthcare platforms and whether customer loyalty factors are correlated with repeat purchase behaviour among these consumers. The study adopted a cross-sectional survey design and used a structured, self-administered questionnaire with a five-point Likert scale to gather data from a sample of 400 consumers of B2C healthcare services in India. Pearson correlation was used to examine the association between digital literacy and the Customer Loyalty Framework (CLF), and simple linear regression was used to examine the relationship between CLF and repeat purchase behaviour. The results indicated that digital literacy and customer loyalty were significantly correlated (r = .286, p < .001). Customer loyalty factors also significantly and positively predicted repeat purchase behaviour (β = .608, B = .742, t = 15.266, p < .001), with the regression model explaining 36.9% of the variance in repeat purchase behaviour (R² = .369, F(1, 398) = 233.065, p < .001). The results show that digital literacy has a positive relationship with loyalty perceptions and that loyalty has a significant relationship with repeat purchase behaviour. The study contributes to the field of digital healthcare by distinguishing digital capability from retention behaviour and adding empirical evidence on customer loyalty and repeat purchase behaviour in the B2C healthcare sector in India.